THE ANALYSIS OF THE VIEWS OF EASTERN SCHOLARS ON THE DEVELOPMENT OF RESEARCH-CREATIVE SKILLS IN CHILDREN (Conferencea, 2025)
This article discusses the introduction of preschool children to the surrounding world, the integration of educational and upbringing matters with nature, and in particular, the views and reflections of ancient manuscripts and Eastern scholars regarding the formation of children's research-creative skills. The works of Eastern naturalist scholars related to the field of acquainting with the environment are examined. The significance and importance of these valuable ideas in the current educational field, as well as their role in the development of children, are highlighted.